2021
DOI: 10.3390/medicina57090924
|View full text |Cite
|
Sign up to set email alerts
|

Existential Suffering in Palliative Care: An Existential Positive Psychology Perspective

Abstract: The COVID-19 pandemic has exposed the inadequacies of the current healthcare system and needs a paradigm change to one that is holistic and community based, illustrated by the healing wheel. The present paper proposes that existential positive psychology (PP 2.0) represents a promising approach to meet the rising needs in palliative care. This framework has a twofold emphasis on (a) how to transcend and transform suffering as the foundation for wellbeing and (b) how to cultivate our spiritual and existential c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 91 publications
0
10
0
Order By: Relevance
“…Bates (2016) suggested that physicians can be trained to address existential suffering so that "it is possible for patients to transition from feeling hopeless to feeling more alive than ever." More recently, Wong and Yu (2021) point out that even the dreaded time of dying can be transformed to a time of deep joy and liberation from human bondage through radical acceptance, faith in God, and support from family and community. That is why the mission of existential positive psychology is to investigate ways to reduce human suffering and transform it into human flourishing (Wong, 2009a(Wong, , 2011(Wong, , 2019a(Wong, , 2021a.…”
Section: Existential Sufferingmentioning
confidence: 99%
See 1 more Smart Citation
“…Bates (2016) suggested that physicians can be trained to address existential suffering so that "it is possible for patients to transition from feeling hopeless to feeling more alive than ever." More recently, Wong and Yu (2021) point out that even the dreaded time of dying can be transformed to a time of deep joy and liberation from human bondage through radical acceptance, faith in God, and support from family and community. That is why the mission of existential positive psychology is to investigate ways to reduce human suffering and transform it into human flourishing (Wong, 2009a(Wong, , 2011(Wong, , 2019a(Wong, , 2021a.…”
Section: Existential Sufferingmentioning
confidence: 99%
“…“Themes common to the descriptions of existential suffering included lack of meaning or purpose, loss of connectedness to others, thoughts about the dying process, struggles around the state of being, difficulty in finding a sense of self, loss of hope, loss of autonomy, and loss of temporality.” This type of suffering calls for different ways of coping and interventions. Bates ( 2016 ) suggested that physicians can be trained to address existential suffering so that “it is possible for patients to transition from feeling hopeless to feeling more alive than ever.” More recently, Wong and Yu ( 2021 ) point out that even the dreaded time of dying can be transformed to a time of deep joy and liberation from human bondage through radical acceptance, faith in God, and support from family and community. That is why the mission of existential positive psychology is to investigate ways to reduce human suffering and transform it into human flourishing (Wong, 2009a , 2011 , 2019a , 2021a ).…”
Section: What Is Existential Positive Psychology? Why Is It Necessary?mentioning
confidence: 99%
“…An examination of optimism in the context of FI in times of a worldwide pandemic requires a complex and dialectical understanding of the balance between positives and negatives, between hope and suffering [ 55 , 56 ]. Therefore, to enhance our understanding of the findings, we conceive 'optimism' not as a state of mere positivity, but rather as a form of 'tragic optimism' - a positive outlook of life that concurrently acknowledges suffering and hardships [ [54] , [55] , [57] , [58] ]. This conceptualization is informed by Victor Frankl's [ 59 ] proposition of 'tragic optimism', defined as optimism in the face of tragedy despite pain, guilt, and death.…”
Section: Discussionmentioning
confidence: 99%
“…However, our recommendation is that optimism should not be discouraged in general. Rather, it should be utilized in a way that integrates the negative with the positive [ 55 ]. In such ways, food-insecure individuals may transform challenges into hopes and genuine changes in their lives.…”
Section: Discussionmentioning
confidence: 99%
“…The model has three notions: firstly, that through suffering existential concerns are revealed during the pandemic; secondly, that existential anxiety damages humanity’s capacity to find meaning in life; and thirdly, that nurturing meaning will alleviate existential anxiety, which will allow human growth and facilitate flourishing. The model can be used by practitioners with those who are suffering during the COVID-19 pandemic by integrating the theory into applied clinical work [ 46 ].…”
Section: Introductionmentioning
confidence: 99%